Acute Inflammatory Demyelinating Polyneuropathy: a comprehensive literature review - Serwońska, Karolina; Pastuszka, Artur; Węgrzyn, Jan; Fijałkowski, Łukasz; Nosal, Aleksandra; Czarnecki, Adam; Galanty-Ochyra, Aleksandra; Zajac, Piotr; Jabłońska, Olga (Journal of Education, Health and Sport, 2025)
Introduction and purpose Guillain-Barré Syndrome (GBS) is an acute, immune-mediated polyneuropathy characterized by rapid-onset muscle weakness and areflexia. It typically follows an infection and can lead to severe complications, such as respiratory failure or autonomic dysfunction. It is a significant concern in neurology and critical care due to its unpredictable course and potential to cause long-term disability. This article aims to present a comprehensive review of Guillain-Barré Syndrome, focusing on its key clinical and prognostic aspects, according to current literature. Description of the state of knowledge Guillain-Barré Syndrome is a complex condition with diverse clinical presentations and pathophysiological mechanisms. It is widely recognized as an immune-mediated disorder, often triggered by infections such as Campylobacter jejuni or cytomegalovirus. The key pathological process involves molecular mimicry, leading to an autoimmune attack on peripheral nerves, resulting in demyelination or axonal damage. Immunotherapy with intravenous immunoglobulin (IVIG) or plasma exchange (PE) is the foundation of treatment, while supportive care is essential for managing respiratory failure and autonomic dysfunction. Conclusions GBS remains a complex condition requiring rapid diagnosis and management. While immunotherapy significantly improves recovery, challenges persist, particularly in the most severe cases. Further research into pathophysiological mechanisms and experimental therapies is essential to refine treatment approaches and improve patient outcomes.